Fungsi Madrasah sebagai Penghubung antara Kerangka Pendidikan Islam dan Pendidikan Nasional - Agus Faisal Asyha (Jurnal Teologi Islam, 2025)
This study aims to analyze the function of madrasahs as bridging institutions between the framework of Islamic education and the national education framework. The research employs a descriptive qualitative approach based on library research by examining primary sources such as the Qur’an, Hadith, the National Education System Law, and regulations issued by the Ministry of Religious Affairs, complemented by secondary sources including books, scholarly articles, and previous studies. The findings reveal that madrasahs play an integrative role across three key dimensions. First, in the epistemological dimension, madrasahs connect revelation-based knowledge with modern scientific knowledge in a harmonious manner. Second, in the curricular dimension, madrasahs integrate the Islamic Religious Education curriculum with the national curriculum through a synthesis of curriculum structure, instructional practices, and character development. Third, in the cultural dimension, madrasahs cultivate Islamic identity while simultaneously strengthening national character and Indonesian values. This study concludes that madrasahs serve as strategic institutions that successfully integrate religious values with national educational demands and are capable of functioning as a model for integrated education in Indonesia